2018
DOI: 10.1534/g3.117.300354
|View full text |Cite
|
Sign up to set email alerts
|

Improving Genomic Prediction in Cassava Field Experiments by Accounting for Interplot Competition

Abstract: Plants competing for available resources is an unavoidable phenomenon in a field. We conducted studies in cassava (Manihot esculenta Crantz) in order to understand the pattern of this competition. Taking into account the competitive ability of genotypes while selecting parents for breeding advancement or commercialization can be very useful. We assumed that competition could occur at two levels: (i) the genotypic level, which we call interclonal, and (ii) the plot level irrespective of the type of genotype, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The increase in ACC for GY and NC were consistent with the marked change in the VCs pattern when including neighbor effects. Improvement of ACC when modeling neighbor effects were also found in the previously mentioned study for cassava where up to 25% increase in accuracy was observed [40]. The ACC obtained in this experiment was expected to be relatively low due to the small size of the population used to train the models.…”
Section: Genomic Prediction and Validationsupporting
confidence: 78%
See 2 more Smart Citations
“…The increase in ACC for GY and NC were consistent with the marked change in the VCs pattern when including neighbor effects. Improvement of ACC when modeling neighbor effects were also found in the previously mentioned study for cassava where up to 25% increase in accuracy was observed [40]. The ACC obtained in this experiment was expected to be relatively low due to the small size of the population used to train the models.…”
Section: Genomic Prediction and Validationsupporting
confidence: 78%
“…For both GY and NC, the RVCs accounted by genomic effects (g) increased considerably but the line effects (l) decreased in the same amount. This indicates that if neighbor effects are excluded from the model a large part of these effects are picked up by the effects of l. In a study for cassava data [40], neighbor effects were investigated as competitive ability. From their simulation study, accuracy in estimating genotypic effects increased when including competitive effects in the model.…”
Section: Estimates Of Variance Components and Heritabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…57 Much subsequent research has focused on the application of genomic prediction to breeding populations [58][59][60] and the elaboration of more flexible models that also include GEIs. [61][62][63][64][65] These models are, however, fundamentally simple, modeling the genotype-phenotype relationship as the sum of additive genetic effects. Increasing complexity by increasing the number of markers, accounting for epistasis, allowing GEIs, and considering non-linear relationships is a challenging statistical and computational problem.…”
Section: Predictive Models For Plant Breedingmentioning
confidence: 99%
“…For example, for potato competition effects between plots consisting of single ridges seems unimportant for yield, as stolons rarely extend beyond ridges (Connolly et al, 1993). For cassava, interplot competition effects have been found to extend beyond the first row (Elias et al, 2018). For sweetpotato, interplot interaction is thought to be substantial due to above-ground competition (Grüneberg et al, 2019).…”
Section: Plot Sizementioning
confidence: 99%